Italianisms in the twenty-second edition of the dictionary of the Spanish language of the Royal Spanish Academy or DRAE - Baldoceda Espinoza, Ana (2014)
This article examines the words of Italian origin incorporated in the 22nd edition of DRAE, noting the treatment they receive in the dictionary and showing the ways how these lexical items have been assimilated into Spanish, the adaptations and variations they have undergone in spelling and pronunciation.We have: a) words taken without adaptation (malaria, piano, piloto); b) with different spelling or pronunciation in Peru (broccoli, ciabatta, salami); c) lack of a diatopical mark in Peru (capo, coliseo, posta médica); d) Italianisms not listed in the DRAE (panetón, menestrón, fuente de soda); e) lack of figurative pronunciation (carpaccio, crescendo, mezzosoprano); f) adaptation of Italian sounds when entering into Spanish: gn > ñ lasagna > lasagna; infinitives ending in /e/ brillare > brillar in initial position of words orconsonant groups /sp-, sf-, sk-/) enter into Spanish with a prosthetic /e/: spaghetti > espaghetti, sfumare > esfumar, scorzonera > escorzonera.